Method for producing thin-film inorganic oxide composite
Patent Information
- Application Number
- JP2022094507
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-10
- Publication Date
- 2025-03-28
AI Technical Summary
Crystalline thin film titanium oxide surfaces can collapse during firing, leading to unevenness and impaired visible light transmission due to scattering, which affects its optical properties.
A method involving coating amorphous thin film titanium oxide with a second inorganic oxide, followed by calcination, to suppress shape collapse and promote crystal transition from anatase to rutile form, enhancing infrared light reflection.
The method effectively prevents shape collapse during high-temperature firing, allowing for improved visible light transmission and enhanced infrared light reflection characteristics.
Smart Images

Figure 00000008_0000 
Figure 00000008_0001 
Figure 00000008_0002
Abstract
Description
Technical Field
[0001] The present invention relates to a thin-film inorganic oxide composite and a method for producing the same.
Background Art
[0002] Crystalline titanium oxide and its composites are widely used in various applications, including cosmetic materials such as ultraviolet ray protectants and pigments. For example, Patent Document 1 discloses an insulating coating titanium oxide structure used in a photoelectric conversion element, in which an insulating oxide film is formed on the surface of a rod-shaped, tubular, fibrous or plate-shaped titanium oxide structure having an average aspect ratio of 3 or more.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] By the way, crystalline thin-film titanium oxide has the property of transmitting visible light while reflecting infrared light, and thus can be used as a cosmetic material utilizing this property. Such crystalline thin-film titanium oxide can be obtained by firing amorphous thin-film titanium oxide to crystallize it. However, during this firing, irregularities may be formed on the surface of the thin-film titanium oxide, resulting in shape collapse. In that case, visible light is scattered by the irregularities on the surface, so there is a problem that the property of transmitting visible light is impaired.
[0005] An object of the present invention is to provide a method for producing a thin-film inorganic oxide composite in which shape collapse during firing is suppressed.
Means for Solving the Problems
[0006] The present invention is a method for producing a crystalline thin-film inorganic oxide composite comprising the following steps 1 and 2. Step 1: A process to obtain an uncalcined composite material in which an amorphous thin film of titanium oxide is coated with a secondary inorganic oxide other than titanium oxide. Step 2: A step of firing the unfired composite obtained in Step 1.
[0007] The present invention is a crystalline thin-film inorganic oxide composite in which a thin film of titanium oxide is coated with a secondary inorganic oxide other than titanium oxide. [Effects of the Invention]
[0008] According to the present invention, by firing an unfired composite material in which an amorphous thin film of titanium oxide is coated with a secondary inorganic oxide other than titanium oxide, it is possible to suppress shape collapse during firing. [Brief explanation of the drawing]
[0009] [Figure 1] This is a scanning electron microscope image of amorphous, thin-film titanium oxide A. [Figure 2] This is a scanning electron microscope image of the crystalline thin-film inorganic oxide composite A1 of Example 1. [Figure 3] This is a scanning electron microscope image of crystalline thin-film titanium oxide A1 from Comparative Example 1. [Figure 4] This is a scanning electron microscope image of the crystalline thin film titanium oxide A2 of Comparative Example 2. [Figure 5] This figure shows the X-ray diffraction patterns of amorphous thin-film titanium oxide A and B, the crystalline thin-film inorganic oxide composites of Examples 1 to 5, and the crystalline thin-film titanium oxide of Comparative Examples 1 and 2. [Modes for carrying out the invention]
[0010] The embodiments will be described in detail below.
[0011] The method for producing a crystalline thin-film inorganic oxide composite according to the embodiment comprises the following steps 1 and 2. Step 1: A process to obtain an uncalcined composite material in which an amorphous thin film of titanium oxide is coated with a secondary inorganic oxide other than titanium oxide. Step 2: A step of firing the unfired composite obtained in Step 1.
[0012] According to the method for producing a thin-film inorganic oxide composite of this embodiment, the collapse of the shape during firing can be suppressed by firing an unfired composite in which amorphous thin-film titanium oxide is coated with a secondary inorganic oxide other than titanium oxide. This is thought to be because the coating with the secondary inorganic oxide suppresses the sintering phenomenon of the thin-film titanium oxide.
[0013] Furthermore, in the thin-film inorganic oxide composite obtained by firing the unfired composite, titanium dioxide is crystallized. When the firing temperature is high, the crystalline form of titanium dioxide undergoes a crystallization transition from anatase to rutile. Titanium dioxide that has undergone this crystallization transition from anatase to rutile exhibits high infrared light reflection properties. Normally, the shape collapse of thin-film titanium dioxide is particularly pronounced at high firing temperatures, but in the manufacturing method of the thin-film inorganic oxide composite according to this embodiment, shape collapse is suppressed even at high firing temperatures. Therefore, by firing at high temperatures, the crystallization transition of titanium dioxide from anatase to rutile can be promoted, thereby improving the infrared light reflection properties.
[0014] Here, "crystallinity" in this application refers to the recognition of a clear crystalline structure of titanium oxide in X-ray crystal structure analysis.
[0015] <Process 1> In step 1, an uncalcined composite is obtained by coating an amorphous thin film of titanium oxide with a secondary inorganic oxide other than titanium oxide.
[0016] The amorphous thin-film titanium oxide can be obtained, for example, by synthesis using a sol-gel transition involving a hydrolysis reaction and a polycondensation reaction. The method for producing the thin-film titanium oxide using this sol-gel transition is disclosed in detail, for example, in Japanese Patent Laid-Open No. 2021-54696.
[0017] From the viewpoints of suppressing shape collapse during firing in Step 2 and promoting crystal transition by firing, the average particle diameter of the thin-film titanium oxide is preferably 1 nm or more, more preferably 0.1 μm or more, still more preferably 1 μm or more. Also, from the same viewpoints, it is preferably 1 mm or less, more preferably 500 μm or less, still more preferably 100 μm or less, and even more preferably 50 μm or less. The average particle diameter of this thin-film titanium oxide is the volume-based average particle diameter measured by the laser diffraction scattering method.
[0018] From the viewpoints of suppressing shape collapse during firing in Step 2 and promoting crystal transition by firing, the average film thickness of the thin-film titanium oxide is preferably 1 nm or more, more preferably 10 nm or more, still more preferably 20 nm or more. Also, from the same viewpoints, it is preferably 100 μm or less, more preferably 10 μm or less, still more preferably 1 μm or less, and even more preferably 500 nm or less. The average film thickness of this thin-film titanium oxide is the number average value of the film thicknesses measured by randomly selecting 100 thin-film titanium oxides from observation photographs taken with a scanning electron microscope.
[0019] From the viewpoints of suppressing shape collapse during firing in Step 2 and promoting crystal transition by firing, the ratio (average particle diameter / average film thickness) of the average particle diameter (average major axis) of the thin-film titanium oxide to the average film thickness is preferably 3 or more, more preferably 5 or more, still more preferably 10 or more. Also, from the same viewpoints, it is preferably 2000 or less, more preferably 1500 or less, still more preferably 1000 or less, and even more preferably 300 or less, and even more preferably 150 or less.
[0020] Examples of the second inorganic oxide include inorganic oxides other than titanium oxide such as tin oxide, silica, cobalt oxide, and iron oxide. The second inorganic oxide preferably contains one or more of these, and more preferably contains an inorganic oxide of Group 14 elements, and even more preferably contains tin oxide, from the viewpoints of suppressing shape collapse during firing in Step 2 and promoting crystal transition by firing.
[0021] Coating of the thin-film titanium oxide with the second inorganic oxide is preferably carried out in a liquid from the viewpoint of performing uniform coating. In this case, from the same viewpoint, it is desirable to use metal chlorides or metal alkoxides as the precursor of the second inorganic oxide. In addition, as a method for coating the thin-film titanium oxide with the second inorganic oxide, there are other methods such as coating by mixing particles of the second inorganic oxide with the thin-film titanium oxide and attaching them to the surface, and methods using a vapor-phase process such as chemical vapor deposition.
[0022] <Step 2> In Step 2, the unfired composite obtained in Step 1 is fired. At this time, crystallization of the thin-film titanium oxide contained in the unfired composite proceeds to obtain a crystalline thin-film inorganic oxide composite.
[0023] From the viewpoint of promoting crystal transition by firing, the firing temperature is preferably 200°C or higher, more preferably 300°C or higher, and even more preferably 400°C or higher. From the viewpoint of suppressing shape collapse during firing, it is preferably 1500°C or lower, more preferably 1200°C or lower, and even more preferably 1000°C or lower.
[0024] From the viewpoint of promoting crystal transition by firing, the firing time is preferably 1 minute or longer, more preferably 10 minutes or longer, and even more preferably 30 minutes or longer. From the viewpoint of suppressing shape collapse during firing, it is preferably 2000 minutes or shorter, more preferably 1800 minutes or shorter, and even more preferably 1500 minutes or shorter.
[0025] The average particle size of the thin-film inorganic oxide composite obtained in step 2 is approximately the same as the average particle size of the thin-film titanium oxide. The average film thickness of the thin-film inorganic oxide composite is also approximately the same as the average film thickness of the thin-film titanium oxide.
[0026] The content of the secondary inorganic oxide in the thin-film inorganic oxide composite is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, from the viewpoint of suppressing shape collapse during firing. Similarly, from the same viewpoint, it is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.
[0027] From the viewpoint of obtaining high infrared light reflectivity, it is preferable that the thin-film inorganic oxide composite contains titanium dioxide with a rutile crystal form, achieved by a crystal transition of titanium dioxide from anatase to rutile. From the same viewpoint, the rutile transition rate from anatase to rutile in the titanium dioxide crystal form contained in the thin-film inorganic oxide composite is preferably 50% or more, more preferably 70% or more. The rutile transition rate is determined by Rietveld analysis in X-ray crystal structure analysis of the thin-film inorganic oxide composite. [Examples]
[0028] (Preparation of thin-film titanium oxide composites and thin-film titanium oxide) Experiments were conducted to prepare crystalline thin-film titanium oxide composites according to Examples 1 to 5 below, as well as crystalline thin-film titanium oxide composites according to Comparative Examples 1 and 2. The composition of each composite is also shown in Table 1.
[0029] <Example 1> An uncalcined amorphous thin film of titanium oxide A was prepared by the same method as in Example 1 disclosed in Japanese Patent Publication No. 2021-54696. Figure 1 is a scanning electron microscope image of this amorphous thin film of titanium oxide A.
[0030] The average particle size of thin-film titanium dioxide A was 13.5 μm. This average particle size is the volume-based average particle size measured by the laser diffraction / scattering method using a laser diffraction / scattering particle size distribution analyzer (LA-960, Horiba, Ltd.). The average particle size was measured by adding an aqueous dispersion of thin-film titanium dioxide A, with a refractive index set to a relative refractive index of 1.12, to a flow cell and measuring the concentration at which the transmittance was approximately 95%.
[0031] The average film thickness of the thin-film titanium oxide A was 156 nm. The average film thickness was determined as follows: A 4.6% by mass aqueous dispersion of thin-film titanium oxide A was prepared. 0.86 g of melamine resin particles (Epostor S6, manufactured by Nippon Shokubai Co., Ltd.) as a bonding inhibitor was added to 4.5 g of this aqueous dispersion. The aqueous dispersion with the added melamine resin particles was heated to a firing temperature of 750°C for 300 minutes under an environment where nitrogen was flowed at a flow rate of 5 L / min, causing water to evaporate, the melamine resin particles to burn off, and the thin-film titanium oxide A to be fired. The obtained thin-film titanium oxide A was observed using a scanning electron microscope. Then, 100 thin-film titanium oxide A samples were randomly selected from the scanning electron microscope images, and their film thicknesses were measured. The average number of these measurements was taken as the average film thickness.
[0032] A first aqueous dispersion was prepared by adding 1 g of thin-film titanium dioxide A to 39 g of water. While stirring, 1 mol / L hydrochloric acid was added to this first aqueous dispersion to adjust the pH to 1.7. The first aqueous dispersion, with a pH of 1.7, was heated to 75°C, and 0.157 g of an 11% by mass tin(IV) chloride aqueous solution was added over 30 minutes. During this process, the tin chloride reaction proceeded, causing the pH to fluctuate; therefore, a 20% by mass sodium hydroxide aqueous solution was added as needed to maintain the pH at 1.7. This first aqueous dispersion was further aged for 30 minutes to generate tin oxide through a redox reaction, thereby obtaining an uncalcined composite A1 in which amorphous thin-film titanium dioxide A was coated with tin oxide. The obtained uncalcined composite A1 was separated by filtration, washed twice with 500 mL of water, and then dispersed in 40 g of water to prepare a second aqueous dispersion. When this second aqueous dispersion was heated and water was scattered, the solid content concentration was measured to be 2.2% by mass.
[0033] 4.5 g of ethanol dispersion containing 9.3% by mass of melamine resin particles as a bonding inhibitor was added to 4.5 g of the second aqueous dispersion. The second aqueous dispersion with the ethanol bonding inhibitor added was heated to a firing temperature of 800°C for 300 minutes under an environment where nitrogen was flowed at a flow rate of 5 L / min, causing the water and ethanol to evaporate, the melamine resin particles as a bonding inhibitor to burn off, and the unfired composite A1 was fired. The firing of this unfired composite A1 caused the thin film titanium oxide A to crystallize, resulting in the acquisition of a crystalline thin film inorganic oxide composite A1. Figure 2 is a scanning electron microscope image of this crystalline thin film inorganic oxide composite A1. The tin oxide content in the obtained thin film inorganic oxide composite A1 was calculated to be 1% by mass, assuming that all tin chloride was converted to tin oxide.
[0034] <Examples 2 and 3> In Examples 2 and 3, the same procedure as in Example 1 was followed, except that the calcination temperature for the second aqueous dispersion was set to 810°C and 825°C, respectively, to obtain crystalline thin-film inorganic oxide composite A2 and thin-film inorganic oxide composite A3, respectively.
[0035] <Example 4> Uncalcined amorphous thin-film titanium oxide B was prepared by the same method as in Example 1 disclosed in Japanese Patent Application Publication No. 2021-54696. The average particle size of the thin-film titanium oxide B was 11.6 μm. The average film thickness of the thin-film titanium oxide B was 137 nm.
[0036] A first aqueous dispersion was prepared by adding 0.5 g of thin-film titanium dioxide B to 19.5 g of water. While stirring, 1 mol / L hydrochloric acid was added to this first aqueous dispersion to adjust the pH to 2.2. The first aqueous dispersion, with a pH of 2.2, was heated to 80°C, and 0.105 g of a 41% by mass tin(IV) chloride aqueous solution was added over 30 minutes. During this process, the tin chloride reaction proceeded, causing the pH to fluctuate; therefore, a 20% by mass sodium hydroxide aqueous solution was added as needed to maintain the pH at 2.2. This first aqueous dispersion was further aged for 30 minutes to generate tin oxide through a redox reaction, thereby obtaining an uncalcined composite B1 in which amorphous thin-film titanium dioxide B was coated with tin oxide. The obtained uncalcined composite B1 was separated by filtration, washed three times with 500 mL of water, and then dispersed in 20 g of water to prepare a second aqueous dispersion. When this second aqueous dispersion was heated and water was scattered, the solid content concentration was measured to be 4.0% by mass.
[0037] 0.93 g of melamine resin particles, a bonding inhibitor, were added to 4.5 g of the second aqueous dispersion. An additional 4.5 g of water was added to improve the dispersibility of the melamine resin. The second aqueous dispersion containing the melamine resin particles was heated to a firing temperature of 750°C for 300 minutes under an environment where nitrogen was flowed at a flow rate of 5 L / min, causing the water to evaporate, the melamine resin particles to burn off, and the unfired composite B1 to be fired. This firing of the unfired composite B1 caused the thin film titanium oxide B to crystallize, resulting in the acquisition of a crystalline thin film inorganic oxide composite B1. The tin oxide content in the obtained thin film inorganic oxide composite B1 was calculated to be 4.8% by mass.
[0038] <Example 5> In Example 5, the same procedure as in Example 4 was carried out, except that 0.418 g of a 41% by mass tin(IV) chloride aqueous solution was added to the first aqueous dispersion to obtain a crystalline thin film inorganic oxide composite B2. The solid content concentration was measured by heating the second aqueous dispersion and scattering the water, and it was found to be 4.5% by mass. The tin oxide content in the obtained thin film inorganic oxide composite B2 was calculated to be 16.7% by mass.
[0039] <Comparative Example 1> 4.5 g of a 4.2% by mass aqueous dispersion of amorphous thin-film titanium oxide A was mixed with 0.80 g of melamine resin particles as a bonding inhibitor. The aqueous dispersion containing the melamine resin particles was heated to a firing temperature of 800°C for 300 minutes under an environment where nitrogen was flowed at a flow rate of 5 L / min, causing the water to evaporate, the melamine resin particles to burn off, and the thin-film titanium oxide A to be fired. The thin-film titanium oxide A crystallized upon firing, resulting in the acquisition of crystalline thin-film titanium oxide A1. Figure 3 is a scanning electron microscope image of this crystalline thin-film titanium oxide A1.
[0040] <Comparative Example 2> In Comparative Example 2, the same procedure as in Comparative Example 1 was followed, except that the calcination temperature for the second aqueous dispersion was set to 825°C, to obtain crystalline thin-film titanium oxide A2. Figure 4 is a scanning electron microscope image of this crystalline thin-film titanium oxide A2.
[0041] [Table 1]
[0042] (Rutile transfer rate) The crystalline forms of amorphous thin-film titanium oxide A and B, crystalline thin-film inorganic oxide composites A1, A2, and A3 of Examples 1 to 3, crystalline thin-film inorganic oxide composites B1 and B2 of Examples 4 and 5, and crystalline thin-film titanium oxide A1 and A2 of Comparative Examples 1 and 2 were analyzed by X-ray crystal structure analysis using dried powder samples.
[0043] X-ray crystal structure analysis was performed using a desktop X-ray diffractometer (MiniFlex 600, Rigaku). The measurement conditions were: X-ray source: Cu / Kα-radiation, tube voltage: 40kV, tube current: 15mA, measurement range: diffraction angle 2θ = 20° to 60°, X-ray scan speed: 10° / min. In X-ray diffraction, a diffraction peak at a diffraction angle (2θ) of 25.4±0.3° was considered to be the anatase type, and a diffraction peak at a diffraction angle (2θ) of 27.5±0.3° was considered to be the rutile type. The percentage of the crystalline form that transitioned from the anatase type to the rutile type, i.e., the rutile transition rate, was determined using Rietveld analysis with the accompanying software. The results are shown in Table 1. Figure 5 shows the X-ray diffraction patterns of amorphous thin-film titanium oxide A and B, Examples 1 to 5, and Comparative Examples 1 and 2 in the X-ray crystal structure analysis.
[0044] (Shape collapse rate) The shape collapse rates of the crystalline thin-film inorganic oxide composites A1, A2, and A3 of Examples 1 to 3, the crystalline thin-film inorganic oxide composites B1 and B2 of Examples 4 and 5, and the crystalline thin-film titanium oxide A1 and A2 of Comparative Examples 1 and 2 were evaluated.
[0045] The shape collapse rate was calculated by randomly selecting 100 samples from scanning electron microscope images of each thin-film inorganic oxide composite or thin-film titanium oxide, classifying them into A, B, and C, and assigning scores of 0 for A, 0.5 for B, and 1 for C, respectively, and then calculating the shape collapse rate based on the following formula. The results are shown in Table 1. A: The surface is smooth. B: Part of the surface is made up of aggregates of particles about 100 nm in size. C: The entire surface is made up of aggregates of particles approximately 100 nm in size. Shape collapse rate (%) ={(Number of A's × 0 + Number of B's × 0.5 + Number of C's × 1) / 100} × 100 [Industrial applicability]
[0046] This invention is useful in the field of thin-film inorganic oxide composites and methods for producing the same.
Claims
1. A method for producing a crystalline thin film inorganic oxide composite, comprising the following steps 1 and 2: Step 1: A step of obtaining an unfired composite in which an amorphous thin film of titanium oxide is coated with a second inorganic oxide other than titanium oxide. Step 2: sintering the unsintered composite obtained in step 1
2. The method for producing a thin film inorganic oxide composite according to claim 1, wherein the crystal type of titanium oxide in the thin film inorganic oxide composite includes a rutile type.
3. The method for producing a thin film inorganic oxide composite according to claim 1 , wherein the second inorganic oxide comprises an inorganic oxide of a Group 14 element.
4. 2. The method for producing a thin film inorganic oxide composite according to claim 1, wherein the average film thickness of the thin film titanium oxide is from 1 nm to 100 μm.
5. 2. The method for producing a thin film inorganic oxide composite according to claim 1, wherein the average particle size of the thin film titanium oxide is from 1 nm to 1 mm.
6. The method for producing a thin film inorganic oxide composite according to claim 1, wherein the content of the second inorganic oxide in the thin film inorganic oxide composite is from 0.01% by mass to 50% by mass.
7. A crystalline thin-film inorganic oxide composite in which thin-film titanium oxide is coated with tin oxide.